Downregulated Serum Exosomal miR-451a Expression Correlates With Renal Damage and Its Intercellular Communication Role in Systemic Lupus Erythematosus - Tan, Lina; Zhao, Ming; Wu, Haijing; Zhang, Yuezhong; Tong, Xiaoliang; Gao, Lihua; Zhou, Lu; Lu, Qianjin; Zeng, Jinrong (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a multi-system autoimmune disease characterized by continuous inflammation and the production of autoantibodies. Exosomes, acting as a critical tool for communication between cells, are involved in the pathogenesis of SLE, particularly in inflammation and immune imbalance. In this study, we aimed to extract and confirm the proinflammatory effect of serum exosomes in SLE. Then, we attempted to find differentially expressed exosomal microRNAs in the serum of healthy subjects and SLE patients via miRNA microarray analysis and validated the target exosomal microRNA, exosomal miR-451a, which expression level decreased in serum of SLE patients by RT-qPCR. Furtherly, we analyzed the correlation between exosomal miR-451a and disease activity, kidney damage and typing, and traditional medicine therapy. Finally, we investigated the intercellular communication role of exosomal miR-451a in SLE by co-culture assay in vitro. Taken together, our study demonstrated that downregulated serum exosomal miR-451a expression correlated with SLE disease activity and renal damage as well as its intercellular communication role in SLE which provided potential therapeutic strategies.